JOURNALISTIC LANGUAGE WRITING STRATEGIES FOR STUDENTS AND BEGINNER WRITERS - Sinta (Journal of English Teaching, Linguistics and Literature, 2020)
Someone who does the writing activity sometimes has a pause or even stops in composing sentences in the writing. Moreover, the person is a beginner writer who has no experience in expressing his thoughts into writing. Journalistic language writing strategies try to get ideas in the face of obstacles that make writing activities hampered. The writings written by the authors are influenced by the understanding they have in presenting their writings about an event. The strategy chosen is expected to be able to make writers become lighter, easier, according to spelling standards, and of course able to solve it. Sometime the mistake made by the writer either intentionally or unintentionally will make a strong reaction to the author's self. A writer must practice first by knowing the strategies, tips, and tricks in order to produce writing that is liked by the general public.